METRICAL INDICES OF THE CECUM WALL IN AREAS OF GUT-ASSOCIATED LYMPHOID TISSUE LOCALISATION UNDER THE INFLUENCE OF FOOD ADDITIVE COMPLEX - Kinash, O.V.; Yeroshenko, G.A.; Shevchenko, K.V.; Slipchenko, L.B.; Vatsenko, A.V.; Riabushko, O.В.; Marchenko, S.P. (World of Medicine and Biology, 2023)
There are insufficient data in the current literature on the effect of food additives on the occurrence of pathological processes in the intestine. A total of 84 sexually mature male non-linear rats were used in the experiment. Rats of the control group consumed drinking water and received oral physiological solution. Animals in the experimental group received food additives at the following doses: sodium nitrite (E250) 0.6 mg/kg, sodium glutamate (E621) 20 mg/kg, ponceau 4R (E124) 5 mg/kg. Sampling for histological examination was carried out at 1, 4, 8, 12 and 16 weeks. A significant reduction in the thickness of the cecum wall of the animals in the areas of localisation of intestinal-associated lymphoid tissue was found at the early stages of observation. A marked lymphoid tissue reaction in the form of intense cellular infiltration of the submucosa and mucosa was recorded. Disturbance of crypt structure and desquamation of epithelium occurred. At the late terms of observation there was a significant increase of the cecum wall thickness in the areas of localization of the lymphoid tissue associated with the intestine due to edema of submucosa, partial restoration of mucosa structures.
Keywords: food additives; monosodium glutamate; sodium nitrite; ponceau 4R; gut-associated lymphoid tissue